PROPERTI DETERMINAN NILAI PERUSAHAAN DAN REAL ESTATE PADA PERIODE GENCARNYA PEMBANGUNAN INFRASTRUKTUR - Fajarnia, Riza; Rimawati, Yuni; Rahmawati, Emi (Jurnal Akuntansi Kontemporer, 2019)
This research aims to obtain empirical evidence about the determinant of firm value property and real estate in the period of incessant infrastructure development. Independent variables used in this research were capital structure as measured by debt to equity ratio (DER), investment opportunity set measured by the market to book ratio (MBA), liquidity measured by the current ratio (CR), and profitability measured by return on equity (ROE). The dependent variable was firm value measured by the price to book value (PBV). Control variable was the size of the firm. The population used in this research are property and real estate companies listed Indonesian Stock Exchange in period 2014-2016. Sample collected using purposive sampling method. The total of 33 companies was determined as the sample during 2014-2016. The method of analysis of this research using multiple linear regression. The result showed that investment opportunity set and profitability has a positive influence on the firm value, and capital structure and liquidity has no effect on the firm value. While the size of the firm as a control variable has a significant positive influence on the firm value.